Cryptocurrencies, national security, crime and terrorism. Issue 2 (3rd March 2020) - Kfir, Isaac
Abstract: This study looks at the challenge that cryptocurrencies could pose to national security as it pertains to terrorism. The study begins by untangling what are cryptocurrencies before shifting attention to how criminal use cryptocurrencies and how terrorist could use cryptocurrencies. One of the key issues identified is the lack of an international regulatory regime, including, a definition of what are cryptocurrencies and how one could regulate the sector. By engaging in such research, this study seeks to encourage international society to focus more on cryptocurrencies and develop an effective, binding regulatory regime.